Analysis of Development Trends of the Research Hotspots of Vitamin D in Children - Luo, Xuemei; Wu, Feifeng; Wang, Cheng; Wen, Chuan (Frontiers in Pediatrics, 2022)
Objective: Using multivariate statistics and social network analysis techniques, we present a realistic and intuitive visualization of the research hotspots and development trends of vitamin D in children. Methods: The Medical Subject Headings (MeSH) term “vitamin D” was used to search all the publications (the study subjects were 0-18 years old) included in PubMed by time period. The subject terms for each development stage were extracted, the high-frequency subject terms were extracted using the Bibliographic Items Co-occurrence Matrix Builder (BICOMB), and a core subject term co-occurrence matrix was established. The Netdraw function of Ucinet 6.0 software was used to complete the social network drawing of the core subject term co-occurrence matrix to form a co-word network diagram composed of core subject terms. Results: Prior to 1979, there were 890 papers with 1,899 core subject terms; from 2010 to 2020, there were 3,773 papers with 12,682 core subject terms. Before 1979, the research direction of vitamin D in children focused on vitamin D in the classical regulation of calcium and phosphorus metabolism. From 1980 to 1989, studies focused on vitamin D metabolites and therapeutic drugs such as “calcitriol” and “calcidiol”. From 1990 to 1999, studies focused on "calcitriol" and its association with "psoriasis", "chronic renal failure" and "dermatological drugs". From 2000 to 2009, studies focused on “vitamin D” and “vitamin D deficiency”. From 2010 to 2020, studies focused on “vitamin D3” and its association with “vitamins”, “bone mineral density protectants”, “asthma”, “obesity”, “pregnancy complications” and “fetal blood”. Conclusion: Since 2010, the research direction of vitamin D in children has been growing rapidly, and the overall development trend is good. Studies extend from the study of the skeletal effect of vitamin D to the study of its extraskeletal effect and the investigation of mechanisms of its association with related diseases.